The Contribution of Lower Local Governments to Health Service Delivery in Kabale Municipality Kabale District: A Case Study of Rushoroza Hospital. - Ayebare, Rosette (Kabale University, 2024)
The issue of unsatisfactory healthcare service delivery is becoming increasingly significant worldwide. Despite the government's efforts to improve the health sector and the achievements of Rushoroza Hospital over the years, the quality of services at the facility is currently declining. It has been reported that admissions often exceed the bed capacity. This study aimed to assess the contribution of lower local governments to health service delivery in Kabale Municipality, using Rushoroza Hospital as a case study. The specific objectives included evaluating the impact of human resources on health service delivery, identifying the main challenges faced by lower local governments in health service delivery, and determining the extent to which healthcare consumables affect service delivery at Rushoroza Hospital in Kabale Municipality. The study employed a case study research design with both qualitative and quantitative approaches. Using simple random and purposive sampling techniques, 89 respondents were selected to participate. Data collection methods included questionnaires and interviews. The findings revealed a strong positive relationship between human resources for health and health service delivery, indicating that adequate human resources are linked to better health service delivery. When analyzing the key challenges faced by lower local governments in health service delivery, there was no significant relationship between these variables (p = 0.249, r = 0.142) since the computed significance value was greater than 0.05. Regarding the effect of healthcare consumables on health service delivery in lower local governments, the results showed a weak positive correlation (p = 0.022, r = 0.277*).